The STRONG Resiliency Program for Newcomer Youth: A Mixed-Methods Exploration of Youth Experiences and Impacts - Claire V Crooks; Nataliya Kubishyn; Maisha M Syeda; Lynn Dare (International Journal of School Social Work, 2020)
Many refugee and immigrant youth face significant adversity, pre- and post-migration, as well as during their migratory journey. Although these youth demonstrate considerable resilience, there is also an opportunity to bolster coping skills and adjustment with group-based interventions in schools. We utilized a mixed-methods approach to describe the impacts of one such program, as experienced by youth (n=19). The program is a ten-session strengths-based resilience intervention that promotes relaxation skills, healthy coping, communication, and problem-solving. There is also one individual session focused on helping each participant share their journey narrative. Youth from six intervention groups participated in this study through completing pre- and post-intervention surveys and focus groups. Our qualitative results identified a high level of acceptability among youth. Perceived benefits included improved coping and relaxation strategies, increased confidence and trust, increased peer connectedness and belongingness, benefits of sharing and exchanging stories with peers, and increased knowledge in the Canadian context. Youths’ scores on resilience and use of STRONG skills increased significantly from pre- to post-intervention, but there was no change in school connectedness scores. We discuss the convergence between qualitative and quantitative findings and highlight some of the areas that were only evident in focus groups. Youth made minor suggestions for program improvement. Based on this small pilot, a resilience intervention resonated with newcomer youth and helped them foster their strengths.
Keywords: resilience; cognitive-behavioral; strength-based; sociotherapy; refugee; youth; adolescence